2009
DOI: 10.1108/00070700910992934
|View full text |Cite
|
Sign up to set email alerts
|

A literature‐based comparison of nutrient and contaminant contents between organic and conventional vegetables and potatoes

Abstract: Purpose: The increasing demand for organic foods is explained mainly by consumers' concerns about the quality and safety of foods and their perception that organically produced foods are healthier and safer than conventional foods. Based on internationally available concentration data of organic and conventional vegetables (carrots, tomatoes, lettuce and spinach) and potato, it was aimed to investigate the scientific validity of nutrition claims as "no vegetable/potato has higher amounts of nutrient X than org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 53 publications
(27 reference statements)
5
53
1
Order By: Relevance
“…The main features of organic farming are claimed to be sustainability, low-impact cropping methods, use of non-chemical fertilizers, and high-quality production; nevertheless, an objective and exhaustive assessment on the supposed higher nutritional value of organic food and on the benefits on consumers' health is still missing. Generally, organic food presents lower nitrates and higher content in vitamin C, but this is not true for all species; spinach, for example, accumulates more nitrates under organic farming than other farming systems [6][7][8]. A literature-based study including potato [7] revealed that organic vegetables are not significantly better than conventional ones and, in addition, experimental findings are often contradictory due to the influence of environmental factors and large genetic diversity among potato varieties tested.…”
Section: Organic Potatoes Production Requires Breedingmentioning
confidence: 99%
See 3 more Smart Citations
“…The main features of organic farming are claimed to be sustainability, low-impact cropping methods, use of non-chemical fertilizers, and high-quality production; nevertheless, an objective and exhaustive assessment on the supposed higher nutritional value of organic food and on the benefits on consumers' health is still missing. Generally, organic food presents lower nitrates and higher content in vitamin C, but this is not true for all species; spinach, for example, accumulates more nitrates under organic farming than other farming systems [6][7][8]. A literature-based study including potato [7] revealed that organic vegetables are not significantly better than conventional ones and, in addition, experimental findings are often contradictory due to the influence of environmental factors and large genetic diversity among potato varieties tested.…”
Section: Organic Potatoes Production Requires Breedingmentioning
confidence: 99%
“…Generally, organic food presents lower nitrates and higher content in vitamin C, but this is not true for all species; spinach, for example, accumulates more nitrates under organic farming than other farming systems [6][7][8]. A literature-based study including potato [7] revealed that organic vegetables are not significantly better than conventional ones and, in addition, experimental findings are often contradictory due to the influence of environmental factors and large genetic diversity among potato varieties tested. Up to date, only few studies focused on organic potatoes and most of them investigated target beneficial (vitamin C, flavonoids, vitamin B1, phenolics) and harmful compounds (heavy metals, glycoalkaloids, nitrates, residues of pesticides), organoleptic properties, and agronomic parameters (yield, tuber size, germination of tubers, starch content).…”
Section: Organic Potatoes Production Requires Breedingmentioning
confidence: 99%
See 2 more Smart Citations
“…For each of the two quality traits (health or environment), two attributes were included in the choice experiment, of which one triggers desirable (positive) expectations and the other undesirable (negative). The choice of the attributes (and their levels) was the result of careful deliberation between the choice experiment preconditions and objective scientific boundaries, the latter based upon an extensive literature review (Hoefkens et al, 2009 andMondelaers et al, 2009). …”
Section: Methodsmentioning
confidence: 99%